University Students’ Attitudes towards using the Nearpod Application in Distance Learning - Musa, Mofeed Ahmed Abu; Momani, Jehad Ali Al (Journal of Education and e-Learning Research, 2022)
Creating a stimulating learning environment is a challenge in distance learning settings. This study aimed to investigate university students' attitudes towards using Nearpod in distance learning. For purposes of the study, the researchers developed a questionnaire of 20 items for which the validity and reliability were verified. The study sample consisted of 190 students. The students were taught different courses remotely in the second semester of the academic year 2020-2021 via Nearpod and Zoom. The results showed that the students had positive attitudes towards using Nearpod. In addition, the results showed that teacher support was the most important variable (x ̅=3.69), while student interaction and participation via Nearpod was predicated by students. Using appropriate applications to increase teacher support and student interaction is the most important variable in distance learning settings. The results also showed that there were no statistically significant differences (α = 0.05) attributed to the gender and academic stage variables.